Upaya Peningkatan Hasil Belajar IPS Melalui Gambar Sebagai Media Pembelajaran - Sujanah Pardede (JURNAL GLOBAL EDUKASI, 2020)
Abstract: This study aims to improve student learning outcomes through pictures as a learning medium on the subject matter Cooperative Social Sciences class IV SDN 010115 Orika kec. People's Island. This class action research was carried out in 2 cycles. The research subjects were grade IV students at SDN 010115 Orika with 23 students. The results of the learning process of learning research with the use of images as learning media as an effort to improve student learning outcomes of Cooperative social studies material material in cycle I reached an average value of 65. After being motivated to do research through cycle II the average value reached 85 means there was an increase of 20. Classical learning completeness in the first cycle reaches 70% after the second cycle classical learning completeness reaches 85% means there is an increase of 15%. It can be concluded that there is an increase in social studies learning outcomes through image media as learning media for fourth grade students at SDN 010115 Orika. Keywords: image media, cooperatives Abstrak: Penelitian ini bertujuan untuk meningkatan hasil belajar siswa melalui gambar sebagai media pembelajaran pada materi Koperasi pelajaran IPS kelas IV SDN 010115 Orika kec. Pulau Rakyat. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus. Subjek peneitian adalah siswa kelas IV SDN 010115 Orika yang berjumlah 23 orang siswa. Hasil proses belajar penelitian pembelajaran dengan pemanfaatan gambar sebagai media pembelajaran sebagai upaya peningkatan hasil belajar siswa materi Koperasi pelajaran IPS pada siklus I mencapai nilai rata-rata 65. Setelah termotivasi dilakukan penelitian melalui siklus II nilai rata-rata mencapai 85 berarti ada peningkatan sebesar 20. Ketuntasan belajar klasikal pada siklus I mencapai 70% setelah siklus II ketuntasan belajar klasikal mencapai 85% berarti ada peningkatan sebesar 15%. Dapat disimpulkan terdapat peningkatan hasil belajar IPS melalui media gambar sebagai media pebelajaran pada siswa kelas IV SDN 010115 Orika. Kata kunci: media gambar, koperasi